2022
DOI: 10.1080/1475939x.2021.2021977
|View full text |Cite
|
Sign up to set email alerts
|

Using online student interactions to predict performance in a first-year computing science course

Abstract: Student performance is a critical factor in determining a university's reputation because it has a negative effect on student retention. Students who do not perform well in a course are more likely to drop out from their programmes before graduating. Many students who enrol in Computing Science programmes struggle to find success because it is considered a difficult discipline. In this study, a sample of 918 observations were selected containing demographic and academic information about students enrolled in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The indices generated by the random index generator cross-over operation take place in terms of several filters [ 1 , 2 ] and the filter size [ 2 , 3 ]. The new child generation of chromosomes is processed based on indices and cross-over operation from parent 1 and parent 2.…”
Section: Proposed Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The indices generated by the random index generator cross-over operation take place in terms of several filters [ 1 , 2 ] and the filter size [ 2 , 3 ]. The new child generation of chromosomes is processed based on indices and cross-over operation from parent 1 and parent 2.…”
Section: Proposed Workmentioning
confidence: 99%
“…Root parents are mutated to produce the new child chromosome using the random index generator. The example considers the number of filters as [ 1 , 4 ] and the size of filters as [ 2 , 3 ].
FIGURE 3 Mutation Operation
…”
Section: Proposed Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Goundar et al [22] applied Decision Tree, Random Forest, Naï ve Bayes, and Support Vector Machine algorithms to build predictive models to determine whether a student will pass or fail the course. The results concluded that the Random Forest algorithm had superior predictive performance capability.…”
Section: Related Workmentioning
confidence: 99%